2020
DOI: 10.1002/cncr.32982
|View full text |Cite
|
Sign up to set email alerts
|

Cancer diagnostic profile in children with structural birth defects: An assessment in 15,000 childhood cancer cases

Abstract: Background Birth defects are established risk factors for childhood cancer. Nonetheless, cancer epidemiology in children with birth defects is not well characterized. Methods Using data from population‐based registries in 4 US states, this study compared children with cancer but no birth defects (n = 13,111) with children with cancer and 1 or more nonsyndromic birth defects (n = 1616). The objective was to evaluate cancer diagnostic characteristics, including tumor type, age at diagnosis, and stage at diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
(68 reference statements)
1
8
0
3
Order By: Relevance
“…In another recent paper, authors investigated stage at cancer diagnosis by birth defects status and did not observe earlier diagnoses of cancer among children with birth defects. 36 Based on these findings, we propose that differential diagnostic scrutiny or disease surveillance does not substantially impact our findings.…”
Section: Discussionmentioning
confidence: 73%
“…In another recent paper, authors investigated stage at cancer diagnosis by birth defects status and did not observe earlier diagnoses of cancer among children with birth defects. 36 Based on these findings, we propose that differential diagnostic scrutiny or disease surveillance does not substantially impact our findings.…”
Section: Discussionmentioning
confidence: 73%
“…HB are reported to occur in association with a wide variety of congenital abnormalities ( Narod et al, 1997 ; Ansell et al, 2005 ; Scollon et al, 2017 ), especially craniosynostosis and renal anomalies ( de Camargo et al, 2011 ), which we also observed in this study. Two recent studies used large population-based linkage data to investigate the association between birth defects and childhood cancer, showing that HB are more prevalent in children with birth defects (5.0% in this group compared to 1.3% in children with cancer; Schraw et al, 2020 ) and frequently occurs in association with craniosynostosis ( Lupo et al, 2019 ). It is interesting that we found in this group of patients a marginally significant result suggesting a tendency of high-risk tumors to develop in patients who also have craniofacial defects.…”
Section: Discussionmentioning
confidence: 99%
“…Still, an explanation for this observation -accidental or causal connection -could not be established (8). The fact that relatively common conditions such as pre-eclampsia, fetal distress before or during childbirth, or congenital malformations could play roles as possible tumor inducers could allegedly be statistically determined in some studies, but an explanation for these observations is still missing (9). Regardless of these observations, over the last few decades, various genetic diseases have been found to be risk factors for developing hepatoblastoma.…”
Section: Etiologymentioning
confidence: 99%